Pengembangan Sistem Monitoring Suhu Berbasis Android untuk Meningkatkan Minat Belajar Fisika - Dwi Jayanti; Irnin Agustina Dwi Astuti; Maria Dewati (UNIVERSITAS INDRAPRASTA PGRI, 2020)
A research development of android-based temperature monitoring systems to increase interest in learning physics has been done. This research aims to determine the feasibility of an android-based temperature monitoring system as a learning media in increasing students' interest in learning physics. Based on the results of the research, the development of an android-based temperature monitoring system is suitable for use as a learning medium and students strongly agree that the media is used as a learning media that can increase interest in learning physics.